2017
DOI: 10.1016/j.celrep.2017.10.055
|View full text |Cite
|
Sign up to set email alerts
|

The Host Protein Reticulon 3.1A Is Utilized by Flaviviruses to Facilitate Membrane Remodelling

Abstract: Flaviviruses are enveloped, positive-sensed single-stranded RNA viruses that remodel host membranes, incorporating both viral and host factors facilitating viral replication. In this study, we identified a key role for the membrane-bending host protein Reticulon 3.1 (RTN3.1A) during the replication cycle of three flaviviruses: West Nile virus (WNV), Dengue virus (DENV), and Zika virus (ZIKV). We observed that, during infection, RTN3.1A is redistributed and recruited to the viral replication complex, a recruitm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
90
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 61 publications
1
90
0
Order By: Relevance
“…Viral proteins interact with DNAJC14, which acts as a chaperone to modulate VP formation (Yi et al, , Yi et al, ), potentially on cholesterol‐rich microdomains (Mackenzie et al, ). We speculate that the viral protein NS4A (based on its predicted topology, structure, and membrane remodelling capacity [Roosendaal et al, , Miller et al, ]) induces membrane curvature while interacting with the host RTN3.1A protein (Aktepe et al, ). We suggest that the biogenesis and recruitment of the cone‐shaped lipids ceramide (Aktepe et al, ) and lyso‐PChol (Liebscher et al, ) stabilises and provides the required curvature for the formation of the VP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Viral proteins interact with DNAJC14, which acts as a chaperone to modulate VP formation (Yi et al, , Yi et al, ), potentially on cholesterol‐rich microdomains (Mackenzie et al, ). We speculate that the viral protein NS4A (based on its predicted topology, structure, and membrane remodelling capacity [Roosendaal et al, , Miller et al, ]) induces membrane curvature while interacting with the host RTN3.1A protein (Aktepe et al, ). We suggest that the biogenesis and recruitment of the cone‐shaped lipids ceramide (Aktepe et al, ) and lyso‐PChol (Liebscher et al, ) stabilises and provides the required curvature for the formation of the VP.…”
Section: Resultsmentioning
confidence: 99%
“…CRISPR and RNA interference screens have identified key host proteins in the replication of many flaviviruses; however, very few studies have subsequently investigated the role of identified proteins in the biogenesis and stability of the viral RC. The reticulon (RTN) protein is the most extensively studied host membrane‐shaping protein during (+)RNA viruses, including WNV and DENV (Aktepe, Liebscher, Prier, Simmons, & Mackenzie, ).…”
Section: Host Membrane‐shaping Proteins During Viral Replicationmentioning
confidence: 99%
See 2 more Smart Citations
“…Cleaved capsid protein interacts with capsid-dense lipid droplets and viral RNA to generate nucleocapsid core followed by Env and prM proteins encapsulation of the nucleocapsid core Invagination of ZIKV-induced vesicles into the ER lumen is mediated through the host reticulon 3.1A (RTN 3.1A) that facilitates ER membrane curvature ( Fig. 1, blue box) [38]. Silencing of RTN3.1A impairs NS4A protein stability and results in significant reduction of virusinduced vesicles and virus replication [38].…”
Section: Zikv Modulates Er Structurementioning
confidence: 99%